'Adrenal rush' in a patient with Neurofibromatosis-1. Issue 3 (3rd May 2020) - Khan, Samiha; Fayyaz, Beenish; Patel, Janki
ABSTRACT: Neurofibromatosis-1 (NF-1) is a genetic neuro-cutaneous disorder that is associated with an increased prevalence of pheochromocytoma (PHEO). However, this association may not be commonly anticipated by physicians, as patients may be normotensive. In addition, NF-1 patients can be asymptomatic and/or normotensive. These factors can result in a delayed or missed diagnosis of pheochromocytoma leading to catastrophic complications. Currently, it is recommended to perform annual blood pressure monitoring in patients with NF-1 and to test for pheochromocytoma only if found to be hypertensive. However, recent studies show that this practice may lead to underdiagnosis of pheochromocytoma. Therefore, suggesting routine biochemical testing for pheochromocytoma in all patients with NF-1. In this case report, we discuss the factors which can lead to a delayed diagnosis of pheochromocytoma in a patient with known NF-1 and hypertension.